Do you want to buy an electric vehicle? examining the consumers' purchase motivation of electric vehicles - Yew, Jun Sen (2023)
This research explores the intricacies of the consumer's purchase intention for an EV in Malaysia, shedding light on the multifaceted factors that shape consumer attitudes and behaviors in response to the global push for sustainable transportation. Placed within the broader context of the evolving automotive landscape, this study employs Partial Least Squares Structural Equation Modeling (PLS-SEM) to comprehensively analyze the relationships between various latent variables derived from directly observed indicators. Notably, the investigation aims to unravel the complexities surrounding consumers' attitudes and behaviors toward EVs in Malaysia, considering the unique socio-cultural and economic factors at play. The findings reveal intriguing dynamics, indicating that while attitudes may not be strong predictors of behavior, perceived behavioral control, subjective norms, and environmental concern emerge as influential factors. Of particular significance is the robust correlation between positive behaviors related to EVs and the intention to purchase. These insights highlight the pivotal roles of individual empowerment, societal influences, and environmental consciousness in steering the trajectory of EV adoption. From a managerial standpoint, the research suggests tailoring interventions to capitalize on these influential factors, while at an industry level, it underscores the necessity for substantial incentives to overcome affordability and infrastructure barriers hindering widespread EV adoption in Malaysia. This study lays the groundwork for future investigations into emerging factors shaping EV adoption dynamics and contributes to the ongoing discourse on sustainable transportation in the region.